Perubahan Organisasi dalam Menghadapi Dinamika Lingkungan Pariwisata - Sri Wahjuni (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
In the competition era, change is the ways of many organizations choose to survive their company. The forms of change depend on the capacity and size of organization in it. The form of organizational changes are; structure, technology, physical setting and people. To develop these capabilities, organizations are forced to rethink how redesign their structures and human resources. For the coming year organizational design needs to be simpler, flatter, more flexible and lateral. Organizations change has impact for management special in tourism industries. Organizations culture is the basic for empowering role of human resource in the dynamic environment. Keywords: change, human resource, tourism